Educação ambiental na prática pedagógica dos professores de um centro municipal de educação infantil de Curitiba - Tavares, Tania Emilene Sieradzki (2016)
This study deals with environmental education in early childhood education, having as a research object the environmental education in teaching practices in the context of early childhood education and as research subjects, teachers who work in a Municipal Center for Early Childhood Education (CMEI) of the Municipal Education Network of Curitiba (RME). Considering that environmental education is necessary in all formal educationlevels, providing the individual, from childhood, a critical view of the socio-environmental context, the guiding question this project tries to answer is:how is the environmental education in pedagogical practices of teachers of a CMEIof the RME of Curitiba constituted? As objectives of this research, general: to analyze the pedagogical practice of environmental education in a CMEI of the RME of Curitiba; and, specific: to know the profile of teachers who work in CMEI of the RME of Curitiba, search field; to characterize the pedagogical practices in environmental education of teachers of a CMEI of the RME of Curitiba and to analyze the connection between environmental education practices carried out by teachers in a CMEI and the school environmental education policy. As a qualitative approach study, the collected data were: documental research and semi structured interviews with teachers working in a CMEI of the RME of Curitiba.The theoretical references of the study consider Layrargues (2002, 2012), Lima (2002), Loureiro (2007, 2009, 2013), Jacobi (2003, 2005), Kramer (1999, 2005), Oliveira (2010, 2012), Angotti (2010), Fazenda (2008), Souza (2006) and Veiga (1995), and other authors that complement this study. The research shows that the environmental education has been expanding on the educational policies and is present in the Curriculum Guidelines for Municipal Education of Curitiba (CURITIBA 2016); environmental education is included neither in the pedagogical proposal of the researched CMEI, nor in the teachers’ planning; training is needed for the early childhood education teachers for the accomplishment of the pedagogical practices in environmental education in critical concept.